Rethinking global history - Gänger, Stefanie; Osterhammel, Jürgen (Cambridge University Press, 2024)
Despite three decades of rapid expansion and public success, global history's theoretical and methodological foundations remain under-conceptualised, even to those using them. In this collection of essays, leading historians provide a reassessment of global history's most common analytical instruments, metaphors and conceptual foundations. Rethinking Global History prompts historians to pause and think about the methodology and premises underpinning their work. The volume reflects on the structure and direction of history, its relation to our present and the ways in which historians should best explain, contextualise and represent events and circumstances in the past. In chapters on fundamental concepts such as scale, comparison, temporality and teleology, this collection will guide readers to assess the extant literature critically and write theoretically informed global histories. Taken together, these essays provide a unique and much-needed assessment of the implications of history going global. This title is also available as open access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 14 Nov 2024).
Keywords: World history -- Philosophy.; History -- Methodology.; Globalization -- History.